1964
DOI: 10.1084/jem.119.2.313
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Simian Papovavirus Sv40

Abstract: The successful use of the fluoropyrimidines to gain information about the synthesis of viral DNA (1-3) led us to a study of their effect on the replication of vacuolating virus (SV40). This agent belongs to the papovavirus group 1 (4) which is characterized by 40 to 50 m/~ icosahedral particles possessing a shell of 42 capsomeres and a core of DNA (5, 6). As the time sequence of virus production in the one-step growth cycle had already been determined for SV40 (7), experiments could be readily designed with 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1965
1965
1977
1977

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…HSV virus-specific antigens and SV40 tumor antigen (T-antigen) were detected by the indirect immunofluorescence technique (Pope and Rowe, 1964;Melnick et al, 1964;Duff and Rapp, 1971a, b). SV40 virus antigen was detected by the direct immunofluorescence test (Melnick et al, 1964).…”
Section: Immunofluorescence Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…HSV virus-specific antigens and SV40 tumor antigen (T-antigen) were detected by the indirect immunofluorescence technique (Pope and Rowe, 1964;Melnick et al, 1964;Duff and Rapp, 1971a, b). SV40 virus antigen was detected by the direct immunofluorescence test (Melnick et al, 1964).…”
Section: Immunofluorescence Assaymentioning
confidence: 99%
“…SV40 virus antigen was detected by the direct immunofluorescence test (Melnick et al, 1964). HSV membrane antigens were also detected by the indirect immunofluorescence test using unfixed cell preparations (Albrecht and Rapp, 1973).…”
Section: Immunofluorescence Assaymentioning
confidence: 99%
“…These late cytoplasmic RNAs probably represent the product of post-transcriptional processing (8,11). During a lytic infection in the presence of various inhibitors of viral and cellular DNA replication, the detection of only early viral RNA has generally been described (12)(13)(14)(15). More recent results supporting the observation that the control of late transcription is dependent on viral DNA replication were reported by Cowan et al (16).…”
Section: Introductionmentioning
confidence: 82%
“…This antigen can be detected by complement fixation and by immunofluorescence techniques (Pope and Rowe, 1964;Rapp et al, 1964a), in sera from hamsters bearing tumors induced by the homologous virus. The same antigen has been found in cells of human and other species following transformation by SV40 Rapp et al, 1964a;Pope and Rowe, 1964;Sabin et al, 1964;Gilden et al, 1965;Habel et al, 1965) and has also been observed during the early phases of the cytolytic cycle of the virus in simian cells (Sabin and Koch, 1964;Rapp et al, 19646;Hoggan et al, 1965;Gilden et al, 1965). The antigen is soluble, thermolabile and serologically distinct from the SV40 capsid antigen Sabin and Koch, 1964;Gilden et al, 1965;Rapp et al, 1964a).…”
mentioning
confidence: 80%